The dynamics of micro and small industries and poverty: A geographical perspective with panel data evidence - Dinar Melani Hutajulu; Fera Febriana Sritutur; Maulia Siti Mukharohmah; Putri Nisrina Damayanti; Aini Fadhilah Dzakirah (Universitas Ahmad Dahlan, 2026)
Despite government efforts, including initiatives like cash transfer programmes, food assistance schemes, and the existence of micro, small, and medium enterprises (MSMEs), poverty remains a persistent problem in Indonesia. Previous studies have yielded conflicting results on the extent to which MSMEs impact poverty reduction efforts. This study examines the effects of micro and small-scale industries on poverty levels in Indonesia, with a particular emphasis on regional disparities between Java and non-Java provinces, as well as between Western and Eastern regions. The analysis utilises panel data from 34 provinces spanning the period from 2017 to 2023, employing panel regression models. The findings indicate that growth in output and employment within small and micro industries is linked to higher poverty levels, suggesting that structural limitations, including low productivity, restricted access to capital, and the prevalence of enterprises focused on survival, hinder their effectiveness in reducing poverty. Research in the region shows that the negative consequence is more apparent in Java and Western Indonesia, primarily due to population pressures and existing wage systems. Unemployment has a significant impact on increasing poverty levels, whereas economic growth helps to decrease them. The Human Development Index (HDI) showed no statistically significant effect. In summary, the research indicates that micro and small enterprises have not yet demonstrated efficacy in poverty alleviation in Indonesia.